Comparison: Imported and Indigenous HIV Fourth-generation immunodiagnostic kits - Rajesh Kumar Sharma; Bharti Chauhan; Ashrat Manzoor; Rajeev Kumar; Daud Ali; Rich Baranwal; Akanksha Bisht; Harish Chander; Anup Anvikar (Asian Journal of Transfusion Science)
Early detection of any disease is always a life-saving methodology for human beings likewise the detection of p24 antigen is always better than the detection of HIV antibodies. In the current era, p24 antigen is added additionally in HIV antibodies detection assays and called HIV fourth-generation immunodiagnostic kit. The different HIV fourth-generation kit having different capacities to pick up the low concentration of analyte as well as represent the detection values in different units. A total of 30 assays were used in this study and it was found that the detection concentration assigned by the manufacturers in the case of imported kits was 0.48 IU/mL to 2 IU/mL. However, the detection range of the indigenous kits was 25 pg/mL to 1000 IU/mL. This study gives an idea/knowledge for the startups concerned with high hope and broad scope for make in India concept in the IVDs market.